1997
DOI: 10.1051/kmae:1997022
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fish assemblages in rivers of the North-Western France : potential consequences for species introductions

Abstract: Introductions of freshwater fish into French rivers have been carried out with increasing frequency in the last decades. Thus, the potential impact of these introductions is of major concern for biologists and fishery managers. Knowledge of the degree of saturation of a community provides an important basis for understanding how the community reacts or will react to the introduction of new species. In this paper, we compare local and regional freshwater fish species richness in similar sizes tributaries and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
19
0
2
Order By: Relevance
“…The degree of degradation in the fish community of the Tiber watershed also appears to be related to the longitudinal gradient. Although studies on the environmental organization of freshwater fish communities in Italy are still limited, some of the trends revealed by our analysis have been described for other geographic areas (AADLAND, 1991;BELKESSAM et al, 1997;LOBB and ORTH, 1991;SCOPPETTONE, 1993;COLLARES-PEREIRA et al, 1995;GODINHO et al, 1997;GODINHO and FERREIRA, 2000). The upper part of the Tiber River basin consists of cold lotic environments, usually characterized by steep gradients.…”
Section: Discussionsupporting
confidence: 52%
“…The degree of degradation in the fish community of the Tiber watershed also appears to be related to the longitudinal gradient. Although studies on the environmental organization of freshwater fish communities in Italy are still limited, some of the trends revealed by our analysis have been described for other geographic areas (AADLAND, 1991;BELKESSAM et al, 1997;LOBB and ORTH, 1991;SCOPPETTONE, 1993;COLLARES-PEREIRA et al, 1995;GODINHO et al, 1997;GODINHO and FERREIRA, 2000). The upper part of the Tiber River basin consists of cold lotic environments, usually characterized by steep gradients.…”
Section: Discussionsupporting
confidence: 52%
“…Relative to this point, results of different studies previously detailed above show that local and regional fish communities are usually not saturated with species and are capable of supporting greater number of species if the pool of potential colonists and the rate of colonization from that pool was increased by species introduction (Belkessam et al, 1997;Angermeier and Winston, 1998;Oberdorff et al, 1998;Gido and Brown, 1999). These results strongly suggest that competition does not set the species saturation level in the assemblages studied and thus that competition is not a major force structuring these fish assemblages.…”
Section: Role Of Biotic Factors Competition and Predationmentioning
confidence: 69%
“…competition, predation, disturbance) were the focus of studies seeking to explain local fish assemblage structure (Schlosser, 1995), emphasis on the role of regional processes has increased as some studies have demonstrated their pervasive role in shaping local assemblages Whittier et al, 1988;Hugheny and Paugy, 1995;Hugueny et al, 1997;Belkessam et al, 1997;Angermeier and Winston, 1998;Oberdorff et al, 1998). Consequently, complete answers for the explanation of local fish assemblage richness and structure must address the relative importance of large-scale processes, which determine the species available to occur locally and small-scale processes, which should limit the number of species that actually occur locally (Angermeier and Winston, 1998).…”
Section: Factors Structuring Riverine Fish Assemblages In Temperate Amentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, chacune des espèces qui compose les peuplements étudiés réagit de façon différentielle aux variations environnementales (différence dans : les périodes de ponte et de recrutement, la distribution sur le gradient vertical, les habitats, la taille des individus et leurs vagilités...) et contribue de la sorte à faire augmenter la variabilité du peuplement à mesure que l'on augmente la durée du suivi. Par ailleurs, à l'échelle locale, les peuplements de poissons des cours d'eau semblent dépendre, en partie, de processus qui s'opèrent à l'échelle régionale (HUGUENY et PAU G Y, 1995 ;BELKESSAM et al, 1997 ;OBERDORFF et al, 1998). …”
Section: Discussionunclassified